Air Component CounterTerrorism Actions and their Impact on VRAEM Development, 2018 - Sanchez Castro, Luis Gustavo (2020)
This research had the general objective of demonstrating the impact of the counter-terrorist actions of the air component on the development of the Valley of the Apurímac, Ene and Mantaro rivers (VRAEM) for the period 2018. The methodology was under the quantitative approach. It was a basic type of research that is located at the explanatory level, using a non-experimental and cross-sectional design, and was correlational in scope. The population was made up of 551,000 inhabitants of the VRAEM, while to select the sample, a statistical calculation was performed considering a finite universe of the population, obtaining a sample of 51 people. The survey was used as a technique and two duly validated and reliable questionnaires as an instrument. The data processing was carried out with the SPSS software (version 23), making the descriptive and inferential analysis by means of ordinal logistic regression, regarding the validation of the hypotheses, the Pearson chi-square test was performed. It was concluded that the counter-terrorist actions of the air component significantly influence the development of the VRAEM, period 2018, due to the likelihood ratio that indicates that the logistics model is significant (p <0.05); it fits the data well (deviation with p <0.05), and explains 64.9% of the dependent variable (development of the VRAEM).